Law as Change Engaging with the Life and Scholarship of Adrian Bradbrook - Babie, Paul (University of Adelaide Press, 2014)
This book brings together those people who worked closely with Bradbrook, each an expert in their own right, to honour a career by critically engaging with the contributions Bradbrook made to property and energy law. Each author has chosen a topic that both fits with their own cutting-edge research and explores the related contributions made by Bradbrook. Most unusually, this collection ranges widely across property law, energy law and human rights.